Partially Plexiform Neurofibroma of the Labia Minora and Clitoral Hood—A Prognostic Dilemma. Issue 3 (July 2015) - Wehmeijer, Leonore M.; Hage, J. Joris; Eberz, Barbara; van Beurden, Marc
Abstract : Background: Unlike solitary neurofibromas, neurofibromatosis type 1 (NF1 or von Recklinghausen disease) has been associated with an increased risk of malignancies. Differentiation between these 2 entities may not be straightforward. Case Report: We present the exceptional case of a girl with one congenital plexiform neurofibroma of the labia minora and clitoral hood in whom the diagnosis NF1 could not been made. Although this presented a prognostic dilemma, we advised against a screening program for any of the malignancies associated with NF1. Still, long-term follow-up seems indicated for recurrence of the partially plexiform neurofibroma and a possible occurrence of malignant peripheral nerve sheath tumor. Abstract : Long-term follow-up after resection of a solitary partially plexiform neurofibroma seems indicated because of possible recurrence and malignant transformation.